Range extension distribution of the frog Hyalinobatrachium fleischmanni (Anura: Centrolenidae) in the state of Puebla and northernmost distribution limit. - Melgarejo-Vélez, Eduardo Y.; Chávez-Ortiz, Maritza; Luría-Manzano, Ricardo; Aportela-Cortés, Daniel; Galicia-Portano, Dulce M.; Canseco-Márquez, Luis; Gutiérrez-Mayén, Guadalupe (Instituto de Ecología, A.C., 2010)
In México, Hyalinobatrachium fleischmanni is distributed in the states of Guerrero, Veracruz, Oaxaca, Chiapas, and Puebla. We provide records from the Sierra Norte of Puebla, which also represent a range extension of 172 km from the only locality known in that state and representing the species´ northernmost distributional record.